Beneficial reuse of Brest-Harbor (France)-dredged sediment as alternative material in road building: laboratory investigations. Issue 5 (4th March 2018) - Maherzi, Walid; Benzerzour, Mahfoud; Mamindy-Pajany, Yannick; van Veen, Eleanor; Boutouil, Mohamed; Abriak, Nor Edine
ABSTRACT: The scarcity of natural aggregates promotes waste reuse as secondary raw material in the field of civil engineering. This article focuses on the beneficial reuse of marine-dredged sediments in road building. Thus, mixtures of raw sediments and dredged sand collected from Brest Harbur (Bretagne, France) were treated with road hydraulic binders. Formulation were prepared and characterized as recommended by the French Technical Guidelines for soil treatment with lime and/or hydraulic binders. Mechanical resistance results are quite similar for both the hydraulic binders, suggesting a similar reactivity with the studied sediment sample. However, some discrepancies can be noted on sustainability parameters. Indeed, water resistance after immersion at 40°C is significantly better for the mixtures treated with cement containing more glass-forming oxides (SiO2 + Al2 O3 ) and fluxing (Fe2 O3 +CaO + MgO + K2 O + Na2 O). Moreover, the both hydraulic binders can lead to swelling in the road materials as observed in scanning electron microscopy analyses. Indeed, microscopic observations indicated volumetric swelling of treated samples, which is greatly influenced on the one side by ettringite quantity and on the other hand by the presence of water in pores material.